Use of new silica fillers as additives for polymers used in packaging of fruit - Arreche, Romina Andrea (2012)
The objective of this work was to synthesize nanosilicas with different degree of hydrophobicity by the sol-gel method, using tetraethyl orthosilicate as a precursor. For this purpose, 3-aminopropyl triethoxysilane (APS) and 1,1,1,3,3,3-hexamethyldisilazane (HMDS), were added during synthesis as modifiers. A commercial biopolymer (Hexamoll Dinch, BASF) intended for packaging of apples, was added to the new nanosilicas. The materials obtained were characterized by X-ray diffraction, scanning electron microscopy, transmission electron microscopy, potentiometric titration, porosity, specific surface area and hydrophobicity/ hydrophilicity by wetting test. Colorimetry was used to evaluate change in apple pulp color after contact with the different silicas.